Digit ratio (2D:4D) predicts sporting success among female fencers independent from physical, experience, and personality factors - Voracek, M.; Reimer, B.; Dressler, S. G. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Research particularly focusing on male athletes and popular sports (running and soccer) suggests associations of lower (masculinized) second-to-fourth digit ratio (2D:4D), a putative marker of prenatal androgen action, with better sports performance. Studies focusing on women, non-mainstream sports, or controlling for covariates relevant for sporting success are still sparse. This study examined associations between 2D:4D and performance of both male and female athletes active in fencing (a non-mainstream sport dominated by male participants), while controlling for covariates. National fencing rankings and 2D:4D of 58 male and 41 female Austrian tournament fencers (mean age 24 years) were correlated. Among female, but not male, fencers, lower 2D:4D was related to better national fencing rankings. 2D:4D still accounted for incremental variance (12%) in fencing success, when the effects of salient performance factors (age, body mass index, years of fencing, training intensity, and the personality variables achievement, control, harm avoidance, and social potency) were controlled for (totaling 35% attributable variance). Athletes active in the most aggressive form (the sabre) had lower 2D:4D than those active in the other forms (épée and foil fencing). Sporting success in adult life might be partly prenatally programmed via long-lasting extragenital effects of testosterone.